Dyeing Properties of Polyester/Cotton Blended Fabric in the Silicone Non-Aqueous Dyeing System. (December 2021) - Pei, Liujun; Jiang, Nan; Wang, Jiping
Polyester/cotton blended fabrics have been extensively used in the textile industry. However, the dyeing process of polyester/ cotton blended fabrics is complex, and a large amount of water is consumed. To increase the dye uptake and dye fixation ratio, and reduce wastewater effluents, the dyeing performance of polyester/cotton blended fabric was studied in one bath and two steps using the silicone non-aqueous dyeing system. When dyeing 1 kg of polyester/cotton blended fabric, only 1.17 kg of water was consumed, and no wastewater was discharged after dyeing. The washing fastness, staining fastness, and dry and wet rubbing fastness of dyed fabric can reach high levels. The dyeing performance of two disperse dyes on the cotton and polyester components in the blended fabric was also studied.